ANALISIS DETERMINAN AUDIT DELAY PADA SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Nurkholik Nurkholik (LPPM UNIVERSITAS BINA INSAN, 2021)
The purpose of this research is to examine the effect of Company Size, Profitability, Solvability and Public Accounting’s Size on Audit Delay. This research used a sample of manufacture companies in the Consumer Goods Industry Sector Food and Beverage Sub Sector which are registered in Indonesia Stock Exchange during 2015 until 2019 period. There are 10 companies used as the sample of the research with an observation period of 5 years. Based on the purposive sampling method, the total of the research sample is 50. The dependent variable of the research is Audit Delay. The independent variable of the research is Company Size, Profitability, Solvability and Public Accounting’s Size. The hypothesis was examined using descriptive statistics, precondition analysis test, multiple linear regression analysis.The result of hypothesis testing on the Company Size, Profitability did not affect the Audit Delay and the Solvability, Public Accounting’s Size affect the Audit Delay.